The effects of placement and geometry on thermo-pneumatic pumping on centrifugal microfluidic compact disc (CD) platforms - Aeinehvand, Mohammad Mahdi; Moebius, Jacob; Harun, Sulaiman Wadi; Abd Rahman, Noorsaadah; Madou, Marc; Ibrahim, Fatimah (2012)
Thermo-pneumatic pumping (TPP) is used to pump fluids on a microfluidic compact disc (CD) to the center of the CD. The expansion of air during heating drives the fluid transfer during TPP. It is easy to fabricate the TPP air chamber and adjoining channel since there are no moving components in their structure and that the thermal energy is supplied to the pump through localized heating equipment. This allows the pumping process even while the disc is rotating. In this report, by changing the shape and placement of the air chamber, we demonstrate that the experimental behavior of the TPP process can be manipulated by the altering heating rate of the air chamber. The placement and geometry of the air expansion chambers affect the rate of transfer during the TPP process. These modifications allow for the customization of the TPP and for a better incorporation onto the microfluidic CD platform, enabling the platform to be more versatile, more complex in functions and countable to be implemented. Â© 2012 IEEE.